HUBUNGAN PENGETAHUAN IBU TERHADAP PERTUMBUHAN ANAK BALITA DI POSYANDU WILAYAH KERJA PUSKESMAS MEKAR BARU KOTA TANJUNG PINANG - Sarita Miguna; Brain Guntoro; Diah Lestari Supardi (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2023)
Background:Parental education and knowledge greatly influence the provision of stimulation, with higher education and knowledge parents can direct children as early as possible and will influence children's intellect to imagine. Growth and development is a continuous process that occurs from conception and continues into adulthood. In the process of reaching adulthood, children must go through various stages of growth and development. Method:The type of research used in this research is a correlational analytic survey with a cross-sectional study approach that examines the relationship between variables and uses a quantitative approach. The sampling technique in this study used accidental sampling with the data analysis technique used was a statistical testwho squares. Results:Statistical test results for the relationship between mother's knowledge and the growth of children under five at Posyandu in the working area of ​​the New Mekar Health Center in Tanjungpinang City have a significant relationship with the obtained test resultschi squarevalued correlation (p value = 0,000). Conclusion:Based on the results of the study, it can be concluded that there is a relationship between mother's knowledge and growth of children under five in the posyandu working area of ​​the new Mekar Health Center in Tanjungpinang City.